Mathematical model of two-phase flow in accelerator channel - Нікулін, О.Ф.; Тітенко, О.М. (Proceedings of National Aviation University, 2010)
The problem of two-phase flow composed of energy-carrier phase (Newtonian liquid) and solid fine-dispersed phase (particles) in counter jet mill accelerator channel is considered. The mathematical model bases goes on the supposition that the phases interact with each other like independent substances by means of aerodynamics’ forces in conditions of adiabatic flow. The mathematical model in the form of system of differential equations of order 11 is represented. Derivations of equations by base physical principles for cross-section-averaged quantity are produced. The mathematical model can be used for estimation of any kinematic and thermodynamic flow characteristics for purposely parameters optimization problem solving and transfer functions determination, that take place in counter jet mill accelerator channel design.